Scenario Foresight Dashboard: transformative modelling pathways for Bangladesh and Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
A set of model results created by the MAGNET model which were based on national scenarios created with participants were made available in an online dashboard. These model results were used with the Planning Commission in Bangladesh to investigate tradeoffs across the SDGs. In Kenya is fully documented and ready.